The Role of Women in Islam - Sahra Indah Rizqiyah; Raden Roro Sri Rejeki Waluya Jati (Gunung Djati Conference Series, 2021)
This study aims to discuss the role of women in Islam. The research method is a qualitative type through literature study by applying content analysis. This research discusses the position, rights, and roles of women in Islam. This research concludes that Islam places women in a noble position, has roles and rights as men. The recommendation of this research is further